Single white female - Leigh, Jennifer Jason, 1962-; Fonda, Bridget; Schroeder, Barbet; Lutz, John, 1939- ([Burbank, Calif.] : Columbia TriStar Home Video, 1997)
In this psychological thriller, New Yorker Allie Jones advertises for a roommate and chooses mousy Hedra Carlson. Hedra takes over Allie's spare bedroom, her clothes, her boyfriend and her identity.
Standard and wide screen formats on opposite sides of disc.
Videodisc release of the 1992 motion picture.
For specific features see interactive menu.
Based on the novel "SWF seeks same" by John Lutz.
Originally produced as motion picture in 1992.
Music, Howard Shore ; associate producer, Susan Hoffman ; production designer, Milena Canonero ; director of photography, Luciano Tovoli ; executive producer, Jack Baran ; screenplay, Don Roos ; producer/director, Barbet Schroeder.
Keywords: Roommates -- New York (State) -- New York -- Drama; Detective and mystery films